Natural Resource Rents-Capital Flight Nexus in Selected ECOWAS Countries: Evidence from Non-Linear ARDL Approach - Adedeji, Abdulfatai A; Kogbodoku, Sherifat W (International Journal of Sustainable Development & World Policy, 2021)
The challenge of capital flight in the ECOWAS sub-region is worrisome. Huge revenue from natural resources also contributes to the relocation of available resources necessary for the development of the region. The study identifies the revenue from natural resources as a key driver of capital flight in the region. Hence, this study analyzed the effect of natural resource rents on capital flight in ECOWAS countries accounting for the role of asymmetry. Also, the study employed the nonlinear autoregressive distributed lag (NARDL) model to account for short-run and long-run asymmetries. The results revealed the presence of asymmetry in five countries, while two countries displayed symmetric effects. It also showed that the symmetric effect of natural resource rents on capital flight is weak for Guinea and Nigeria in the short-run while the long-run effect is not more pronounced for Nigeria. In the case of asymmetric effect, natural resource rents amplified capital flight in Cape Verde and Sierra Leone. Further evidence shows that the non-linearity of natural resource rents does not encourage capital flight in Burkina Faso, Cote d’Ivoire, and Ghana. Hence, the countries should promote transparency and accountability in the management of proceeds from natural resources to enhance development in the region.